Therapeutic effects of adipose-derived stem cells pretreated with pioglitazone in an emphysema mouse model - Hong, Yoonki (Exp Mol Med, 2016)
There is no therapy currently available that influences the natural history of disease progression in patients with chronic obstructive pulmonary disease (COPD). Although stem cell therapy is considered a potential therapeutic option in COPD, there are no clinical trials proving definitive therapeutic effects in patients with COPD. Recently, it was reported that pioglitazone might potentiate the therapeutic effects of stem cells in patients with heart or liver disease. To test the capacity of pioglitazone pretreatment of stem cells for emphysema repair, we evaluated the therapeutic effects of pioglitazone-pretreated human adipose-derived mesenchymal stem cells (ASCs) on elastase-induced or cigarette smoke-induced emphysema in mice. We also investigated the mechanisms of action of pioglitazone-pretreated ASCs. Pioglitazone-pretreated ASCs had a more potent therapeutic effect than non-pretreated ASCs in the repair of both elastase-induced and smoke-induced emphysema models (mean linear intercept, 78.1±2.5 μm vs 83.2±2.6 μm in elastase models and 75.6±1.4 μm vs 80.5±3.2 μm in smoke models, P<0.05). Furthermore, we showed that pioglitazone-pretreated ASCs increased vascular endothelial growth factor (VEGF) production both in vitro and in mouse lungs in the smoke-induced emphysema model. Pioglitazone-pretreated ASCs may have more potent therapeutic effects than non-pretreated ASCs in emphysema mouse models.